Physical activity in Poland and the European Union - Metelski, Adam (Quality in Sport, 2019)
The primary purpose of the article is to present the level of sport participation in Poland and other European Union countries. Moreover, the article discusses the definitions of individual terms related to sport, determinants of physical activity and plans of increasing participation in sport in Poland and across the European Union. The article uses data provided by extensive public opinion polls as well as by abundant Polish and English literature on the subject. The results of the research show that in Poland, when compared to the European Union, a lower percentage of people are actively involved in sport. However, it can be noted that in recent years there has been a growing interest in physical activity in Poland.